2022
DOI: 10.3390/su14106204
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Evolution Dynamic, Effect and Governance Policy of Construction Land Use in Urban Agglomeration: Case Study of Yangtze River Delta, China

Abstract: The urban construction land change is the most obvious and complex spatial phenomenon in urban agglomerations which has attracted extensive attention of scholars in different fields. Yangtze River Delta Urban Agglomeration is the most mature urban agglomeration in China, a typical representative in both China and the world. This paper analyzes the evolution dynamic, effect and governance policy of urban construction land in Yangtze River Delta Urban Agglomeration 2011–2020 using a combination of BCG model, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 149 publications
0
0
0
Order By: Relevance
“…The green space data cover the built-up area inside and outside of the city, and it is difficult to determine the unique characteristics of the changes in the spatial pattern of the green space landscape in the areas outside the built-up area. For example, Zhang Li-Quan et al [37] quantitatively revealed the spatial distribution characteristics of the landscape pattern in Shanghai. With the help of GIS spatial analysis technology, Zhang et al [38] studied the typical regional green corridor space in Shanghai, constructed an evaluation system, and provided a scientific and effective basis for the development of regional green corridors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The green space data cover the built-up area inside and outside of the city, and it is difficult to determine the unique characteristics of the changes in the spatial pattern of the green space landscape in the areas outside the built-up area. For example, Zhang Li-Quan et al [37] quantitatively revealed the spatial distribution characteristics of the landscape pattern in Shanghai. With the help of GIS spatial analysis technology, Zhang et al [38] studied the typical regional green corridor space in Shanghai, constructed an evaluation system, and provided a scientific and effective basis for the development of regional green corridors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang Li-Quan et al quantitatively revealed the spatial distribution characteristics of the landscape pattern in Shanghai. With the help of GIS spatial analysis technology, Zhang et al [37] studied the typical regional green corridor space in Shanghai, constructed an evaluation system, and provided a scientific and effective basis for the development of regional green corridors. The overall lack of spatial characterization of regional green landscapes outside the built-up area prevents regional ecological environment construction [38].…”
Section: Discussionmentioning
confidence: 99%
“…The decoupling theory was first proposed by the Organization for Economic Cooperation and Development (OECD) [4], and Tapio introduced the elasticity method to the decoupling theory to study the decoupling relationship between economic growth and carbon emissions in the European transport sector [5]; the model was later widely used to explore the relationship between resource consumption and environmental pollution. At present, a large number of scholars have applied the decoupling model at the international [6,7], national [8][9][10][11][12][13], regional [14][15][16][17], urban [18,19], and industrial levels [20][21][22][23]. For example, Zhao et al analyzed the decoupling relationship between carbon emissions and economic development for 29 countries, based on the Tapio model, and the study found some differences in the decoupling status among countries in each period.…”
Section: Introductionmentioning
confidence: 99%